Hubungan Kualitas Layanan Elektronik dan Kualitas Informasi Aplikasi Halodoc Terhadap Kepuasan pada Pengguna - Fadia Eka Septiawati; Puteri Fannya; M. Fuad Iqbal; Lily Widjaja (Lembaga Pengembangan Kinerja Dosen, 2024)
User satisfaction with the Halodoc application is measured by meeting user needs. The halodoc application is a health application which has many features and uses, one of which is that patients can chat and communicate with specialist doctors who are experienced in their respective fields. This research aims to determine the relationship between the quality of electronic services and the quality of the Halodoc application information on user satisfaction. Researchers also use the DeLone and McLean information system success model by taking several necessary variables. The samples used by researchers were users of the halodoc application or had used the halodoc application. The data collection instrument uses a questionnaire where the questionnaire is distributed digitally. The questionnaire is distributed in December 2023 - January 2024. Hypothesis testing is carried out by examining the relationship between electronic service quality and information quality on user satisfaction using the Chi-Square test, the research results show that service quality electronics and information quality have a relationship with user satisfaction.